Rasmussen’s Encephalitis in Children: A Case Report - Akter, Naznin; Mushrraf, Mashura (Bangladesh Journal of Child Health, 2023)
Rasmussen’s Encephalitis (RE) is one form of chronic and progressive focal encephalitis of children presented with intractable epilepsy and progressive neurologic deficits. The cause of the disease is still unknown but thought to be an immunological disorder following a viral infection. Brain imaging is one of the best tools for diagnosis. We presented a case of Rasmussen’s encephalitis. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 35-38